17th Greek Film Festival - Greek Orthodox Community of New South Wales; Bank of Cyprus (Australia); Greek Film Festival 2010 : Sydney, N.S.W.); Greek Festival of Sydney 2010 : Sydney, N.S.W.) ([Lakemba, N.S.W.] : Greek Orthodox Community of NSW, 2010)
Colour lithographic poster advertising the 17th Greek Film Festival events to be held in Sydney from 14-30 October 2010 at the Palace Norton Street Cinemas, Leichhardt. The Festival is a cultural celebration of Greek-Australian lifestyle, culture and heritage, however its appeal is much broader reflecting the rich and diverse multicultural nature of Australia and it has evolved into an important Greek-Australian community event in NSW. The poster image is of a tall pile of maroon boxes for ‘papers’, stacked up against a wall painted in white, beige and grey. The floor in the foreground is scattered with papers and boxes with a small bright pink teddy bear in the centre.
Caption title.
"Sydney, 14-31 October 2010"--At foot of poster.
"An initiative of the Greek Orthodox Community of NSW"--Above logos.
"Presented by Bank of Cyprus Australia"--Below caption title.
Logos of: Greek Orthodox Community of NSW ; Greek Festival of Sydney.
"www.greekfilmfestival.com.au"--Below caption.
Keywords: Film festivals -- New South Wales -- Sydney -- Posters; Film posters -- New South Wales -- Sydney -- Posters; Film posters, Australian; Posters, Australian; Australia -- Posters; Australian